ANALISIS KEAMANAN SISTEM PEMBELAJARAN ONLINE MENGGUNAKAN METODE ISSAF PADA WEBSITE UNIVERSITAS XYZ - Andhika Wisnu Wardhana (2021)
University XYZ e-learning website is an internet-based application that is easy to use anywhere and anytime using only a browser, either via smartphone or computer. E-learning stores student data such as assignments, quizzes, and others. In the midst of the Covid-19 pandemic, e-learning websites are increasingly being visited because lecture activities are conducted online. Due to the importance of using the e-learning website, to anticipate threats to the University XYZ e-learning website, the researcher will test the security of the University XYZ e-learning website. Website security testing is carried out using the Web Penetration Testing method. The framework used in testing penetration testing of the University XYZ e-learning website is the ISSAF framework. The ISSAF framework is a penetration testing standard used to test the resilience of websites. The purpose of this study was to determine whether there is a security gap on the University XYZ e-learning website. From the results of this test, the results of the report and the provision of recommendations will be given to the University XYZ IT administrator. This research is expected to help University XYZ IT administrators to develop more secure website security.